2006
DOI: 10.1007/s00381-006-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and focal brain stem tumors in childhood: prognostic factors and surgical outcome

Abstract: Fourteen patients were diagnosed as having DBSTs. The responses to treatment were ten cases of partial response, three of stable disease, and one of progressive disease. General and/or neurological symptoms improved in more than 80% of patients. The median time from diagnosis to progression and to death were, nonetheless, 8 (range of 3-13) and 13 (range of 4-25) months, respectively, with a 2-year overall survival rate of 12.3% [standard error (SE) 11.2]. Seventeen patients were diagnosed as having FBSTs. Gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
4
43
3
Order By: Relevance
“…Similar to our results, the study found the extent of resection to be an important prognostic factor ( P = 0.012). 20 Our study found the OS at 5 and 10 years to be 90% and 75%, respectively, in patients with focal brainstem gliomas. In addition, our study confirmed the prognostic significance of tumor location, even when controlling for similar low-grade histology, with pontine tumors fairing the worst.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Similar to our results, the study found the extent of resection to be an important prognostic factor ( P = 0.012). 20 Our study found the OS at 5 and 10 years to be 90% and 75%, respectively, in patients with focal brainstem gliomas. In addition, our study confirmed the prognostic significance of tumor location, even when controlling for similar low-grade histology, with pontine tumors fairing the worst.…”
Section: Discussionmentioning
confidence: 46%
“…This group found in a cohort of 17 patients with focal brainstem gliomas the 4-year overall and disease-free survival rates to be 87.4% and 58.8%, respectively. 20 Patients were treated with a combination of surgery, RT, and chemotherapy. Similar to our results, the study found the extent of resection to be an important prognostic factor ( P = 0.012).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to cranial nerves and vasculature can result in diffuse neurological deficits and additional surgeries/treatments prolonging recovery time and decreasing quality of life. Due to the location of these tumors, surgery has often been difficult to achieve and thus radiation therapy has been the treatment of choice [13]. However, advances in surgical equipment and techniques has made surgical resection of these tumors possible and have been shown to improve the survival outcomes of patients with these types of tumors [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the location of these tumors, surgery has often been difficult to achieve and thus radiation therapy has been the treatment of choice [13]. However, advances in surgical equipment and techniques has made surgical resection of these tumors possible and have been shown to improve the survival outcomes of patients with these types of tumors [13, 14]. Our findings also indicate that surgery yielded a more favorable outcome with patients receiving a radical surgical resection and partial/subtotal resection living longer than those who did not, with 1-year survival rates of 96.3, 94.8, and 67.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, focal brainstem tumor are typically approached for biopsy or resection. 8,25 Recent evidence that 11 has raised the issue of targeted therapy and with it some renewed interest in obtaining tumor tissue to tailor treatment to specific cellular expression in infiltrating brainstem tumors. Roujeau et al 24 recently demonstrated that stereotactic biopsy of diffuse brainstem gliomas was associated with minimal morbidity and yielded highly diagnostic tissue samples that would allow precise tumor characterization necessary for participation in new treatment protocols.…”
Section: Discussionmentioning
confidence: 99%